2012
DOI: 10.1001/archinternmed.2011.580
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Medical Home Characteristics and Staff Morale in Safety Net Clinics

Abstract: Background We sought to determine whether perceived patient-centered medical home (PCMH) characteristics are associated with staff morale, job satisfaction, and burnout in safety net clinics. Methods Self-administered survey among 391 providers and 382 clinical staff across 65 safety net clinics in 5 states in 2010. The following 5 subscales measured respondents’ perceptions of PCMH characteristics on a scale of 0 to 100 (0 indicates worst and 100 indicates best): access to care and communication with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 20 publications
1
87
1
Order By: Relevance
“…1 A study using crosssectional methods found that patient-centered medical home attributes were associated with lower morale at a group of safety net clinics, 36 although there is evidence that improvements in quality and care delivery at safety net clinics are associated with higher morale and lower burnout when there is adequate staffing, fair distribution of responsibility, and training infrastructure. 37 Keeping a focus on team culture could enhance the effects of practice transformation on work life experiences.…”
Section: Discussionmentioning
confidence: 99%
“…1 A study using crosssectional methods found that patient-centered medical home attributes were associated with lower morale at a group of safety net clinics, 36 although there is evidence that improvements in quality and care delivery at safety net clinics are associated with higher morale and lower burnout when there is adequate staffing, fair distribution of responsibility, and training infrastructure. 37 Keeping a focus on team culture could enhance the effects of practice transformation on work life experiences.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 A recent study compared internal medicine residents' likelihood of entering GIM as a result of clinic to likelihood of entering a career in GIM before clinic, and demonstrated that 28 % were less likely to enter GIM as a result of their clinic experience, 59 % had no difference in likelihood, and only 11 % were more likely to enter general IM as a result of clinic. 34 Current attempts to improve the outpatient clinic experience include the development of patientcentered medical homes and accountable care organizations, 35,36 efforts to decrease panel size, and the creation of multidisciplinary, inter-professional teams. 10 These changes should help to train residents in team environments that allow physicians to work at the peak of their training levels and in more satisfying work conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10 These changes should help to train residents in team environments that allow physicians to work at the peak of their training levels and in more satisfying work conditions. 36 Additionally, increased support of non-face to face patient care encounters as well as ambulatory payment reforms 37 might entice debt-ridden residents 38,39 to enter the primary care field.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, Nutting and colleagues reported change fatigue, including burnout and turnover, among participants in the National Demonstration Project, 27 and Lewis and colleagues found greater PCMH characteristics associated with high staff morale, but also higher provider burnout, among 65 safety-net clinics in a 2010 survey. 28 Moreover, organizational research has previously found workplace change-particularly frequent change or multiple changes-associated with greater burnout. 29,30 In addition to offering conflicting findings, the existing literature on PCMH implementation and burnout is limited by small sample sizes, generally restricted to PCMH demonstration sites, and a focus almost exclusively on the physician experience.…”
Section: Introductionmentioning
confidence: 99%